Příčiny, průběh a důsledky americké hypoteční a světové finanční krize - Stelzerová, Tereza (2010)
This study is focused on the causes of financial crises in the United States of America starting in 2007. There is mentioned a number of influences that had impact on this disfavourable economic development in this study. In the first part, there is mentioned the housing policy and government measures in providing mortgages. Further, there is explained the development of the banking system -- with the Federal Reserve System on one hand and commercial banks on the other. Their parts in this crises are explained in the second chapter, alongside with modern trends on financial markets. One of those trends was occurrence of new kinds of securities -- eg. CDO which is characterized. Rating agencies were also subjects which business behavior was one of the causes of this crises burst. In this study there is also captured simple line-out of events on the interbank market, when the crises became obvious. Last part is dedicated to comparison with other crisis of the modern history, especially the Great Depression.